UPAYA TOKOH OGINO GINKO MENCAPAI KESETARAAN GENDER DALAM NOVEL HANAUZUMI KARYA JUNICHI WATANABE - Giri Prastasari, Ni Luh (Humanis, 2014)
Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 This undergraduate thesis entitled "Ogino Ginko’s Efforts to Reach Gender Equality In Hanauzumi Novel by Junichi Watanabe" is analyzed using the theory of ideological feminist literary criticism and supported by the concept of gender. Based on the analysis that has been done, Ogino Ginko experienced gender discrimination, such as marginalization, subordination, stereotyp, violence, and double workload as well. Ogino Ginko’s efforts to achieve gender equality can be seen from the purpose of her life, her attitude towards the discrimination she experienced, and her position as a woman doctor in Japanese society. /* Style Definitions */ table.MsoNormalTable {mso-style-name:"Table Normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:0cm; mso-para-margin-bottom:10.0pt; mso-para-margin-left:0cm; line-height:115%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi;}
Keywords: feminism, gender, ideological feminist literary criticism